ECOLOGICAL GOODS MARKET: CONCEPTS AND MAIN FEATURES - Трішкіна, Ніна; Бузніцька, Ірина (SWorldJournal, 2026)
The article examines the features and trends in the development of the ecological goods market. The interpretation of the concept of “ecological goods” by domestic and foreign scientists is analyzed. The author’s vision of this concept is proposed. The ke